The Availability, Methodological Soundness, and Scope of Consumer Price Statistics in 2020 - Guerreiro, Vanda (IMF Working Papers; Working Paper ;, 2022)
This paper analyzes the availability, methodological soundness, and scope of Consumer Price statistics in IMF member and non-member countries in 2020. Consumer price statistics are instrumental in the development of monetary policy and in monitoring economic developments. They also often have administrative uses such as in determine wage increase or seting pension payments. This analysis examines the appropriateness of the current set of global consumer price statistics for current policy development and highlights regions where further development may be required. The analysis is based on the results of a new annual survey of CPI compilation practices in 207 economies as of the end of 2020. The survey was completed by statistical authorities between March 2021 and June 2021. In cases of non-response, IMF staff estimates were used. IMF Staff estimates were based on information taken from the IMF's Dissemination Standards Bulletin Board (DSBB) and country websites to provide the status of consumer price index compilation practices. These data summarize the following key aspects; i) Production, publication and scope of the Consumer Price Index Program, ii) Data sources, iii) CPI compilation methods and iv) Concepts and classifications.